(untitled) - Alan J Cann (San Diego, California, 1997)
The book provides an essential introduction to modern virology. Focusing on a molecular approach, this book presents the principles of virology in a clear concisemanner; explores and explains the fundamental aspects of virology including; structures of virus particles and virus genomes, virus replication, control of gene expression, virus pathogenesis (including AIDS), detailed and up-to-date discussion of prion diseases. This book is expanded and has been completely with many figures and tables, which complement the text. The summaries and self-assessment questions at the end of each chapter provide excellent revision aids
Keywords: gene expression regulation, viral,Genome, viral,Virus diseases,Virus replication,Viruses; Physiology